Development and validation of a culturally adapted teacher leadership scale based on TLMS in Chinese private universities - Qianqian Suna; Mohd Khairuddin Abdullah @Jerry Abdullah; Tan Choon Keong (Persatuan Sains Sosial dan Kemanusiaan Muallim, 2025)
This study developed and validated a culturally adapted Teacher Leadership Scale based on the Teacher Leadership Model Standards (TLMS) tailored to faculty in Chinese private universities. A quantitative cross-sectional design was employed, involving expert review, pretesting, and both exploratory and confirmatory factor analyses using data from 300 faculty members. The final instrument consisted of 28 items across seven domains, demonstrating strong internal consistency (α = 0.927) and excellent model fit (RMSEA = 0.017, CFI = 0.993). The results confirmed the theoretical validity and contextual relevance of the TLMS framework in a non-Western higher education setting. This validated tool supports future research and institutional practice in teacher leadership development.